2014
DOI: 10.3109/13697137.2014.937688
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogens induce differential effects on both normal and malignant human breast cellsin vitro

Abstract: This study demonstrates that phytoestrogens have antiproliferative effects on breast cancer cells via an ER-dependent mechanism, even at low concentrations, but are also capable of maintaining the survival of normal breast cell via ER-independent or other mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 27 publications
0
23
0
1
Order By: Relevance
“…Thus, the effects of phytoestrogens were mainly proven in human breast cancer cell lines. In addition to other studies, our previous study demonstrated that genistein, resveratrol and quercetin do not stimulate MCF‐7 breast cancer cells and may induce apoptosis even at low concentrations . However, cancers are well known for high heterogeneity .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Thus, the effects of phytoestrogens were mainly proven in human breast cancer cell lines. In addition to other studies, our previous study demonstrated that genistein, resveratrol and quercetin do not stimulate MCF‐7 breast cancer cells and may induce apoptosis even at low concentrations . However, cancers are well known for high heterogeneity .…”
Section: Discussionmentioning
confidence: 76%
“…These phytoestrogens have a lower binding affinity to ER α but also exert partial anti‐estrogenic effect, due to their relative binding preference to ER β . Our previous study demonstrated that the dichotomy of classic ER modulating action induced by these phytoestrogens may result in different effects on mammalian tissue . However, as of now, the effects of phytoestrogen have been mainly proven in human breast cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies revealed that the distinctive expression of ER α and ER β may be associated with the apoptotic effects of these phytoestrogens (higher affinities for ER β) and the proliferative effect of E 2 in MCF-7 breast cancer cells (13,14). 8 necessary for proliferation and that ER β opposes the proliferative effects exerted by ER α (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…These phytoestrogens have a lower binding affinity to ER α, but also exert partial anti-estrogenic effect due to their relative binding preference to ER β (11, 12). Our previous study demonstrated that the dichotomy of classic ER modulating action induced by phytoestrogens may result in different effects on mammalian tissue (13,14). However, in the presence of endogenous estrogen, the potential effects induced or modulated as a result of these phytoestrogens and their ER binding capabilities is a cause for concern.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from numerous in vitro and in vivo studies has confirmed an ability of phytoestrogens, such as RSV, to modulate various targets and signaling pathways in a wide range of conditions such as cancer or cardiovascular diseases; they also inhibit cell proliferation in breast cancer cells via different mechanisms, including an ERec‐dependent mechanism. Moreover, RSV is able to maintain the survival of normal cells via ERec‐independent or other mechanisms . Despite RSV well‐documented health benefits, its mechanism of action remains controversial.…”
Section: Discussionmentioning
confidence: 99%